Pengembangan Kecerdasan Spiritual Anak Melalui Lagu-lagu Islami - Romadatul Fitriyah; Bastami Bastami (Fakta: Jurnal Pendidikan Agama Islam, 2021)
An educator has an important role in guiding and following children, they are required to be able and willing to provide various stimuli in accordance with the potential intelligence of the child. One form of stimulation of Halimah Kindergarten students is taught various forms and types of Islamic nuances known as pats and songs. The songs and claps that are taught include the songs of the names of angels, the pillars of Islam, the pillars of faith and the songs of prayer and so on. By using Islamic songs in the learning process students will be more motivated, faster in learning the material and organize them compared to using conventional methods. Based on the context, the researcher focuses on "How to develop children's spiritual intelligence through Islamic songs in group B TK Halimah Prenduan Praga Sumenep in the 2019-2020 Academic Year as well as supporting and inhibiting factors. The approach used in this research is a qualitative field approach. The methods used are interview, observation, and documentation methods. The results showed that the implementation of Islamic songs in the development of children's spiritual intelligence in group B TK Halimah Prenduan Praga Sumenep Academic Year 2019-2020 which is classified into preparation, material and delivery, props and evaluation are all good. The supporting factors include educators, the environment and learning resources. Meanwhile, the inhibiting factors include time constraints, classroom layout constraints, and tools for singing.